2021
DOI: 10.1200/jco.2021.39.3_suppl.228
|View full text |Cite
|
Sign up to set email alerts
|

KEYlargo: A phase II study of first-line pembrolizumab (P), capecitabine (C), and oxaliplatin (O) in HER2-negative gastroesophageal (GE) adenocarcinoma.

Abstract: 228 Background: Gastric and esophageal adenocarcinomas are a leading cause of cancer death worldwide. Many of these patients (pts) present with locally advanced unresectable or metastatic disease and are treated with combination cytotoxic chemotherapy. Single agent P is FDA approved for patients with recurrent locally advanced or metastatic gastric or gastroesophageal junction adenocarcinoma (GEJ) whose tumors have a combined positive score (CPS) ≥ 1 after disease progression on or after two lines of therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Upfront chemotherapy with checkpoint inhibition recently demonstrated positive results in GEC in several clinical trials. The KEYlargo, phase II, single-arm trial evaluating first line pembrolizumab with CapeOx in GEC recently reported interim results showing an excellent ORR of 72.7%, mPFS of 7.6 months, and mOS of 15.8 months with a grade 3-4 treatment-related adverse events of 44% [31]. Furthermore, the ongoing ATTRACTION-4, phase II/III trial is evaluating nivolumab with chemotherapy (oxaliplatin with S-1 or capecitabine) in Asian patients.…”
Section: Immunotherapy Trials In Gastroesophageal Cancermentioning
confidence: 99%
“…Upfront chemotherapy with checkpoint inhibition recently demonstrated positive results in GEC in several clinical trials. The KEYlargo, phase II, single-arm trial evaluating first line pembrolizumab with CapeOx in GEC recently reported interim results showing an excellent ORR of 72.7%, mPFS of 7.6 months, and mOS of 15.8 months with a grade 3-4 treatment-related adverse events of 44% [31]. Furthermore, the ongoing ATTRACTION-4, phase II/III trial is evaluating nivolumab with chemotherapy (oxaliplatin with S-1 or capecitabine) in Asian patients.…”
Section: Immunotherapy Trials In Gastroesophageal Cancermentioning
confidence: 99%